(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nowadays, distance Learning system is becoming more popular in India and all around the world. Distance education is growing tremendously day by day. There is a huge scope of distance education in future. This mode of education attracts the people who are currently engaged in job and want to pursue higher education along with their career.Formerly, Distance Education Council (DEC) coordinates the distance learning institutes and maintains the standard of distance learning. In December 2012, all the responsibilities regarding the regulation of distance education has been transferred to University Grants Commission (UGC).Distance Education is inexpensive provides opportunities to the students to enhance their qualifications. In the last couple decades, Distance Learning has evolved a lot. With the advancement of technology, distance learning is now also includes e-learning or online learning.